Direct Spectroscopic Detection of Key Intermediates and the Turnover Process in Catalytic H2 Formation by a Biomimetic Diiron Catalyst. Issue 47 (1st August 2019) - Wang, Shihuai; Pullen, Sonja; Weippert, Valentin; Liu, Tianfei; Ott, Sascha; Lomoth, Reiner; Hammarström, Leif
Abstract: [FeFe(Cl2 ‐bdt)(CO)6 ] (1 ; Cl2 ‐bdt=3, 6‐dichlorobenzene‐1, 2‐dithiolate), inspired by the active site of FeFe‐hydrogenase, shows a chemically reversible 2 e − reduction at −1.20 V versus the ferrocene/ferrocenium couple. The rigid and aromatic bdt bridging ligand lowers the reduction potential and stabilizes the reduced forms, compared with analogous complexes with aliphatic dithiolates; thus allowing details of the catalytic process to be characterized. Herein, time‐resolved IR spectroscopy is used to provide kinetic and structural information on key catalytic intermediates. This includes the doubly reduced, protonated complex 1H −, which has not been previously identified experimentally. In addition, the first direct spectroscopic observation of the turnover process for a molecular H2 evolving catalyst is reported, allowing for straightforward determination of the turnover frequency. Abstract : In the moment : Time‐resolved IR spectroscopy provided structural and kinetic information on several intermediates in the catalytic cycle of a proton reduction catalyst (see figure). This allowed direct monitoring of the final, rate‐determining step (RDS) of H−H formation, which provided a straightforward way to determine the turnover frequency.